Measurement of Sunspot Proper Motion Using Cross-Correlation Method - Clara Yono Yatini; Soshinori Suematsu; Emanuel Sungging Mumpuni (Jurnal Matematika & Sains, 2003)
Cross-correlation method is a technique for determining the vector displacement that maximizes the spatially local cross-correlation between an image and a reference image as a continuous function of the image space. The crosscorrelation is defined as a function of position in the image, within a spatially localized apodization window. This method is applied to measure the proper motion of the sunspot accurately which can be calculated from a series of active region images as a function of time. This method gives a measure of the spot displacement unaffected by the jitter of the telescope.